2018
DOI: 10.1126/science.aao6047
|View full text |Cite
|
Sign up to set email alerts
|

BAK/BAX macropores facilitate mitochondrial herniation and mtDNA efflux during apoptosis

Abstract: Mitochondrial apoptosis is mediated by BAK and BAX, two proteins that induce mitochondrial outer membrane permeabilization, leading to cytochrome c release and activation of apoptotic caspases. In the absence of active caspases, mitochondrial DNA (mtDNA) triggers the innate immune cGAS/STING pathway, causing dying cells to secrete type I interferon. How cGAS gains access to mtDNA remains unclear. We used live-cell lattice light-sheet microscopy to examine the mitochondrial network in mouse embryonic fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
529
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 721 publications
(560 citation statements)
references
References 81 publications
30
529
1
Order By: Relevance
“…Indeed, they found that treatment of cells with BCL‐2 targeting drugs, called BH3 mimetics, was able to stimulate the release of the pro‐inflammatory cytokines IL‐6, IL‐8, CXCL1 and FGF‐2 in the absence of cell death. Consistent with recent findings, this pro‐inflammatory phenotype was dependent on BAX/BAK and STING (McArthur et al , ; Riley et al , ). Accordingly, they found that depleting cells of mtDNA, using a mitochondrial‐targeted viral DNase, was able to reduce IL‐6 secretion following BH3‐mimetic treatment.…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Isupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, they found that treatment of cells with BCL‐2 targeting drugs, called BH3 mimetics, was able to stimulate the release of the pro‐inflammatory cytokines IL‐6, IL‐8, CXCL1 and FGF‐2 in the absence of cell death. Consistent with recent findings, this pro‐inflammatory phenotype was dependent on BAX/BAK and STING (McArthur et al , ; Riley et al , ). Accordingly, they found that depleting cells of mtDNA, using a mitochondrial‐targeted viral DNase, was able to reduce IL‐6 secretion following BH3‐mimetic treatment.…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Isupporting
confidence: 91%
“…Mitochondrial permeabilisation elicits inflammation in multiple ways. For instance, recent work shows that mtDNA is ejected from permeabilised mitochondria during cell death, activating cGAS‐STING‐dependent type I interferon production (McArthur et al , ; Riley et al , ). While dispensable for cell death, apoptotic caspases serve to dampen inflammation by targeting multiple cellular processes (McIlwain et al , ; Ning et al , ).…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Imentioning
confidence: 99%
“…Little IL‐6 secretion was seen in melanoma cells where apoptosis signaling was inhibited by Bcl‐X L (Fig F and G). Mitochondrial DNA (mtDNA) may, when released into the cytosol (McArthur et al , ), trigger a cytokine response through the cyclic GMP‐AMP synthase (cGAS) and the stimulator of interferon genes (STING) (Rongvaux et al , ; White et al , ). We therefore generated a HeLa cell line where mtDNA was degraded upon tamoxifen‐regulated expression of a viral DNase (HSV‐1 UL 12.5) targeted to mitochondria (Corcoran et al , ) (Fig H).…”
Section: Resultsmentioning
confidence: 99%
“…CCs do not activate platelets directly or induce clotting of full blood (C. Shi, T. Kim, S. Steiger, S. R. Mulay, B. M. Klinkhammer, T. Bäuerle, M. E. Melica, P. Romagnani, L. Yang, D. Möckel, M. Baues, E. Mammadova‐Bach, B. Sanne, J. W. M. Heemskerk, A. Braun, T. Lammers, P. Boor, H. J. Anders, unpublished observation) but trigger mechanical injury to endothelial cells and activate complements, which leads to the release of tissue factor and nuclear DNA both initiating the clotting process (C. Shi, T. Kim, S. Steiger, S. R. Mulay, B. M. Klinkhammer, T. Bäuerle, M. E. Melica, P. Romagnani, L. Yang, D. Möckel, M. Baues, E. Mammadova‐Bach, B. Sanne, J. W. M. Heemskerk, A. Braun, T. Lammers, P. Boor, H. J. Anders, unpublished observation). The indirect activation of platelets increases the amount of prothrombotic extracellular DNA as activated platelets release mitochondrial DNA (C. Shi, T. Kim, S. Steiger, S. R. Mulay, B. M. Klinkhammer, T. Bäuerle, M. E. Melica, P. Romagnani, L. Yang, D. Möckel, M. Baues, E. Mammadova‐Bach, B. Sanne, J. W. M. Heemskerk, A. Braun, T. Lammers, P. Boor, H. J. Anders, unpublished observation) . Also, NETs partially contribute to this process (C. Shi, T. Kim, S. Steiger, S. R. Mulay, B. M. Klinkhammer, T. Bäuerle, M. E. Melica, P. Romagnani, L. Yang, D. Möckel, M. Baues, E. Mammadova‐Bach, B. Sanne, J. W. M. Heemskerk, A. Braun, T. Lammers, P. Boor, H. J. Anders, unpublished observation).…”
Section: How Do Crystals Trigger Thrombosis?mentioning
confidence: 99%